1993
DOI: 10.1017/s0003356100006796
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction in continuously underfed Brahman cows

Abstract: This experiment examined the effects of sustained levels of undernutrition applied to grazing Brahman heifers on subsequent lifetime reproductive performance. Weaned heifers were raised to a target weight of 270 kg at three different stocking rates to obtain contrasting weight gains (0·097 kglday, L = low; 0·215 kg/day, M = medium; 0·259 kg/day, H = high). They were then subjected to common grazing in a low-quality Brachiaria humidicola pasture, where mean weight changes ranged between -0.100 and +0·300 kg/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 3 publications
4
12
0
Order By: Relevance
“…The observed LWs at reconception (Table 5) showed moderate variability, as estimated by the confidence limits, and did not differ between CW and EW treatments. These LWs are similar to those reported by Vera (1991;282-300 kg) for the first conception of heifers grazing Brachiaria humidicola, and are slightly below the LWs at the second to fourth conception recorded by Vera et al (1993;325-340 kg) for cows grazing that same pasture. They therefore appear to be the lower limit for viable conceptions carried to term in cattle of the same phenotype as used here, and extrapolating from Vera et al (1993) they are also dangerously close to the calculated asymptotic LW allowed for on low quality rangelands.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The observed LWs at reconception (Table 5) showed moderate variability, as estimated by the confidence limits, and did not differ between CW and EW treatments. These LWs are similar to those reported by Vera (1991;282-300 kg) for the first conception of heifers grazing Brachiaria humidicola, and are slightly below the LWs at the second to fourth conception recorded by Vera et al (1993;325-340 kg) for cows grazing that same pasture. They therefore appear to be the lower limit for viable conceptions carried to term in cattle of the same phenotype as used here, and extrapolating from Vera et al (1993) they are also dangerously close to the calculated asymptotic LW allowed for on low quality rangelands.…”
Section: Discussionsupporting
confidence: 85%
“…These LWs are similar to those reported by Vera (1991;282-300 kg) for the first conception of heifers grazing Brachiaria humidicola, and are slightly below the LWs at the second to fourth conception recorded by Vera et al (1993;325-340 kg) for cows grazing that same pasture. They therefore appear to be the lower limit for viable conceptions carried to term in cattle of the same phenotype as used here, and extrapolating from Vera et al (1993) they are also dangerously close to the calculated asymptotic LW allowed for on low quality rangelands. These values can be compared with the mature body sizes of well-fed and highly fertile cows grazing well managed B. decumbens pastures, that ranged between 388 and 452 kg (Vera et al 2002).…”
Section: Discussionsupporting
confidence: 85%
“…However, the authors observed that the model underpredicted LWGs compared to our measured records. In summary, as suggested above, cow-calf systems in the Orinoco basin are complex and multidimensional (Ezzano 2005;Vera et al 1993Vera et al , 2002Vera and Ramírez Restrepo 2017). However, the present paper has only touched on a small number of their characteristics, whereas others related to additional environmental and social impacts have been addressed elsewhere (Hoogesteijn and Chapman 1997;Navas-Ríos 1999).…”
Section: Discussionmentioning
confidence: 79%
“…In contrast, young cattle (i.e. 1-3 years of age) are low priority categories in extensive systems and are relegated to low quality pastures, whereas in more intensive grazing systems young females are generally bred before reaching 3 years of age (Vera et al 1993;Vera et al 2002). The most prominent additional feature of this cattle productive system is that older cows are culled following weaning and/or during the dry season, when they have lost 15 to 25% of the LW recorded at conception as described by Vera et al (2002).…”
Section: Discussionmentioning
confidence: 99%
“…Body condition score (HCS) is an easy and reliable measure to be used in the nianagement of cow feeding according to physiological status. Seasonal variation on pasture availability-xauses changes i n animal body weight and BCS, limiting reproductive potential, mainly during the dry season, when cows do not have enough food for maintenance and other physiological 23 processes, such as reproduction (Rae et al, 1993;Vera et al, 1993).…”
Section: Introductionmentioning
confidence: 99%